The Effectiveness of Psychoeducation on Effective Communication in Adolescent Parenting - Fildzah Hanifati; Djudiyah (Journal of Scientific Research, Education, and Technology (JSRET), 2026)
This study aimed to evaluate the effectiveness of a psychoeducational program on effective communication in adolescent parenting in improving the quality of parent-adolescent communication. A quantitative approach with a one-group pretest-posttest design was employed. The participants consisted of 11 parents who were members of the Bina Keluarga Remaja (BKR) Mentikan 2 community group in Mojokerto City, Indonesia. Communication quality was assessed using the Parent-adolescent Communication Scale (PACS), which measures the dimensions of Open Communication and Problem Communication. Data were analyzed using the Wilcoxon Signed Rank Test. The results indicated a significant increase in Open Communication scores (Z = -2.941, p = .003) and a significant decrease in Problem Communication scores (Z = -2.552, p = .011). In addition, the program evaluation demonstrated positive participant ratings regarding the learning materials, facilitator, instructional methods, perceived benefits, and overall program implementation. The findings suggest that psychoeducational on effective communication has the potential to enhance the quality of parent-adolescent communication within community-based parenting programs.